The Effect of comparison of Jackfruit Seed Flour with Starch and Sodium Bicarbonate on Crackers Quality - Sri Efriyanti Harahap; Terip Karo-Karo; Linda Masniary Lubis (Universitas Sumatera Utara, 2014)
This study was conducted to find the best amount of of jackfruit seed flour with tapioca and the best amount of sodium bicarbonate to produce crackers. Research was done using completely randomized design with two factors, namely the comparison of jackfruit seed flour wheat and tapioca flour (T): (1:3, 1:6, 1:9, and 1:12) and the amount of sodium bicarbonate (S): (0,5%, 1%, and 1,5%). Parameters analyzed were moisture content, ash content, fat content, protein content, the degree of development and the value of organoleptic (color, aroma, flavor and crispness). The results showed that the ratio of jackfruit seed flour and tapioca flour had highly significant effect on all parameters. The amount of sodium bicarbonate had a highly significant effect on water content, ash content, protein content, fat content, and degree of development of sensory crispness. The interaction between comparative jackfruit seed flour with tapioca flour had a highly significant effect on water content, ash content, protein content, fat content, organoleptic crispness, and the different degrees of development but had no significant effect on the organoleptic taste, color and aroma. Keywords: Crackers, jackfruit seed flour, tapioca starch, sodium bicarbonate.